2022
DOI: 10.3390/ijms24010338
|View full text |Cite
|
Sign up to set email alerts
|

Role Played by Paraoxonase-2 Enzyme in Cell Viability, Proliferation and Sensitivity to Chemotherapy of Oral Squamous Cell Carcinoma Cell Lines

Abstract: Oral squamous cell carcinoma represents the most aggressive and frequent form of head and neck cancer. Due to drug resistance, the 5-year survival rate of patients with advanced disease is less than 50%. In order to identify molecular targets for effective oral cancer treatment, we focused on paraoxonase-2 enzyme. Indeed, based on data previously obtained from preliminary immunohistochemistry and Western blot analyses performed on tissue specimens, the enzyme was found to be upregulated in tumor compared with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 52 publications
2
17
0
Order By: Relevance
“…The increased expression of PTGS2 , KDR , VEGFB and CXCR1 in samples from patients with positive recurrence can be explained by their association with treatment resistance. Inflammation caused by PTGS2 promotes the survival of cancer cells and their resistance to therapy because inflammatory cells can create inflammatory mediators that support cell survival and confer resistance to therapies that cause cell death 40 . Overexpression of PTGS2 can prevent apoptosis (programmed cell death), contributing to treatment resistance 41 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increased expression of PTGS2 , KDR , VEGFB and CXCR1 in samples from patients with positive recurrence can be explained by their association with treatment resistance. Inflammation caused by PTGS2 promotes the survival of cancer cells and their resistance to therapy because inflammatory cells can create inflammatory mediators that support cell survival and confer resistance to therapies that cause cell death 40 . Overexpression of PTGS2 can prevent apoptosis (programmed cell death), contributing to treatment resistance 41 .…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation caused by PTGS2 promotes the survival of cancer cells and their resistance to therapy because inflammatory cells can create inflammatory mediators that support cell survival and confer resistance to therapies that cause cell death. 40 Overexpression of PTGS2 can prevent apoptosis (programmed cell death), contributing to treatment resistance. 41 Inflammatory cytokines that activate CXCR1 can activate downstream signalling pathways that improve cancer cell survival and increase resistance to certain treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear Factor Erythroid 2-Related Factor 2 (NFE2L2 or NRF2)/Kelch Like ECH Associated Protein 1 (KEAP1) signalling is one of the most important pathways involved in chemoresistance onset and cancer progression [14,57,58]. In fact, NRF2 can bind the antioxidant response element (AREs) regions present in the promoter of several antioxidant genes such as NQO1, superoxide dismutase (SOD), catalases (CATs), thioredoxins (Trxs), peroxiredoxins (Prxs), reductases and peroxidases inducing their expression and counteracting the oxidant effects of platinum-based chemotherapeutics, then leading to chemoresistance in these cells [14,57,[59][60][61].…”
Section: Nqo1 Cellular Modulators In Ovarian Cancermentioning
confidence: 99%
“…Thus, Nakamura et al [ 30 ] investigated ribosomal stress and hypoxia in oral cavity tumors, whereas Ferreira et al [ 31 ] explored the role of targeting lysosomes in colorectal cancer. Campagna et al [ 32 ] reported an interesting study regarding the role of paraoxonase-2, an enzyme with a debated role in tumorigenesis, in oral squamous cell carcinomas, whereas in another interesting review article, the possibility to target the isoprenoid biosynthetic pathway in multiple myeloma is presented in detail [ 33 ]. An overview of metabolism and signal transduction in cancer cells was presented by Chae and Hong [ 34 ], who stressed the fact that metabolism of cancer cells is thoroughly relevant both for the design of novel therapies and for the outcome of the existing ones [ 35 , 36 ].…”
Section: State Of the Artmentioning
confidence: 99%